Schiff Base Synthetic Coating from The Chitosan Acylation of Green Mussel Shell (Perna viridis) as A Corrosion Inhibitor in Reinforcing Steel - Lukvy, Wisely; Yuwono, Arief Sabdo; Putra, Heriansyah (Jurnal Teknik Sipil dan Lingkungan, 2024)
Reinforced concrete is widely used in construction implementation in Indonesia. The use of reinforcing steel as a structural material has the potential to experience corrosion. A Schiff base is one of the compounds considered a potential corrosion inhibitor. Green mussel (Perna viridis) contains chitosan which can produce chitosan Schiff base. This study aimed to analyze chitosan, Schiff base, optimum inhibitor concentration, and morphological structure. This research consisted of extraction and acylation transformation stages, corrosion rate measurement, and SEM testing. This research resulted in the degree of deacetylation of chitosan from the FT-IR spectra of 53.71%. Chitosan Schiff base from green mussel shells was successfully synthesized as much as 188.41 g. The optimum corrosion rate is found at the inhibitor concentration of 1500 ppm, with the highest efficiency level of 91.84%. The results of SEM testing on treated steel samples yielded fewer corrosion products in the form of uniform corrosion and pitting corrosion than untreated steel samples. This result shows that the chitosan Schiff base inhibitor from the optimum concentration of green mussel shells effectively inhibits the corrosion rate.